The impact of recreational cannabinoid legalization on utilization in a pregnant population - Torres, Jacob; Miller, Colton; Apostol, Michael; Gross, Jessica; Maxwell, Jessie R. (Frontiers in Public Health, 2024)
Background: Marijuana potency and utilization both continue to increase across the United States.While the overall prevalence of cannabinoid utilization during pregnancy has been surveyed in various studies, the direct impact of changing governmental policies on pregnancy use is less characterized. Thus, we aimed to investigate how the legalization of recreational cannabinoid products impacted use during pregnancy in the state of New Mexico.Methods: Participants who had a live birth during two study epochs were included: pre-legalization